Extracorporeal Membrane Oxygenation in COVID-19 Treatment: a Systematic Literature Review - Tatiana Farias de Oliveira; Carlos Alberto de Oliveira Rocha; Aisla Graciele Galdino dos Santos; Luiz Carlos Francelino Silva Junior; Saulo Henrique Salgueiro de Aquino; Euclides José Oliveira da Cunha; Rafaela Campos Alcântara; Rodrigo da Rosa Mesquita; Gabriel Monteiro Arnozo; Fernanda Mayara Santos Santana; Etvaldo Rodrigues da Silva Filho; Carlos Dornels Freire de Souza (Brazilian Journal of Cardiovascular Surgery, 2021)
Abstract Introduction: The present study intends to systematically review the literature on the use of extracorporeal membrane oxygenation (ECMO) in patients with coronavirus disease 2019 (COVID-19). Methods: The research was carried out according to the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Studies were selected from PubMed/MEDLINE and LILACS databases between December 2019 and May 17 2020, using the descriptors "ECMO AND COVID-19", "Extracorporeal Membrane Oxygenation AND COVID-19", "ECLS AND COVID-19", and "Extracorporeal Life Support AND COVID-19". Exclusion criteria were government epidemiological bulletins, comments, literature reviews, and articles without full access to content. Results: Two hundred and thirty-three scientific productions were found, however only 18 did not met the exclusion criteria and could be included in this study, amouting to a total of 911 patients - 624 (68.5%) men, 261 (28.6%) women, and 26 (2.8%) without sex information. The mean age of the patients was 53.7 years. ECMO was necessary in 274 (30.1%) people (200 [73%] submitted to veno-venous ECMO, nine [3.3%] to veno-arterial ECMO, and seven [2.5%] moved between these two types or needed a more specific ECMO according to the disease prognosis). Five studies did not specify the type of ECMO used, amounting 57 (20.8%) patients. Five patients (1.8%) were discharged, 77 (28.1%) died, 125 (45.6%) remained hospitalized until publication time of their respective studies, and 67 patients (24.4%) had no outcome information. Conclusion: It is evident that more research, covering larger populations, must be carried out in order to clearly elucidate the role of ECMO in the treatment of COVID-19.